2017
DOI: 10.1111/wvn.12239
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and Empowering Direct‐Care Nurses to Promote EBP: An Example of Evidence‐Based Policy Development, Education, and Practice Change

Abstract: This column shares the best evidence-based strategies and innovative ideas on how to facilitate the learning and implementation of EBP principles and processes by clinicians as well as nursing and interprofessional students. Guidelines for submission are available at http://onlinelibrary.wiley.com/journal/10.1111/(ISSN)1741-6787.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
3
1
1
Order By: Relevance
“…Pre-covid period published researches showed strong importance and support to the direct use of innovative research results in the nursing practice [32], and even have introduced strategies to empower nurse practitioners on evidence-based practices [44,48]. Though this present study found no factors (personal and professional) correlated to research utilization, contrary was found in some others.…”
Section: Discussioncontrasting
confidence: 72%
“…Pre-covid period published researches showed strong importance and support to the direct use of innovative research results in the nursing practice [32], and even have introduced strategies to empower nurse practitioners on evidence-based practices [44,48]. Though this present study found no factors (personal and professional) correlated to research utilization, contrary was found in some others.…”
Section: Discussioncontrasting
confidence: 72%
“…The empowerment of NAs might lead to greater participation in planning, decision-making, and interdisciplinary teams, all activities being required of NAs across healthcare settings [ 8 ]. Importantly, NAs who feel empowered tend to perform their duties better, have higher morale and job satisfaction rates, and are less likely to consider leaving their jobs [ 9 11 ]. The benefits of an empowered NA workforce are especially important during a crisis in which quickly changing organizational practices related to empowerment are likely to shape the psychological experiences of empowerment; however, little is known about this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…8 Importantly, NAs who feel empowered tend to perform their duties better, have higher morale and job satisfaction rates, and are less likely to consider leaving their jobs. [9][10][11] The bene ts of an empowered NA workforce are especially important during a crisis in which quickly changing organizational practices related to empowerment are likely to shape the psychological experiences of empowerment; however, little is known about this relationship.…”
Section: Introductionmentioning
confidence: 99%